2014
DOI: 10.1093/hmg/ddu058
|View full text |Cite
|
Sign up to set email alerts
|

New insights into POLE and POLD1 germline mutations in familial colorectal cancer and polyposis

Abstract: Germline mutations in DNA polymerase ɛ (POLE) and δ (POLD1) have been recently identified in families with multiple colorectal adenomas and colorectal cancer (CRC). All reported cases carried POLE c.1270C>G (p.Leu424Val) or POLD1 c.1433G>A (p.Ser478Asn) mutations. Due to the scarcity of cases reported so far, an accurate clinical phenotype has not been defined. We aimed to assess the prevalence of these recurrent mutations in unexplained familial and early-onset CRC and polyposis, and to add additional informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
131
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 22 publications
6
131
0
Order By: Relevance
“…In a recent study, the same POLE variant was also detected as a de-novo occurrence in a patient with early onset CRC and polyposis. 14 Interestingly, the germline POLE variant in the currently studied families (PT1, PT2 and PT3) is associated with a Lynch syndrome phenotype with MSI tumours and MSH6 or MSH2/MSH6 protein loss. This contrasts with previously identified POLE and POLD1 germline variant carriers who developed microsatellite stable tumours.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In a recent study, the same POLE variant was also detected as a de-novo occurrence in a patient with early onset CRC and polyposis. 14 Interestingly, the germline POLE variant in the currently studied families (PT1, PT2 and PT3) is associated with a Lynch syndrome phenotype with MSI tumours and MSH6 or MSH2/MSH6 protein loss. This contrasts with previously identified POLE and POLD1 germline variant carriers who developed microsatellite stable tumours.…”
Section: Resultsmentioning
confidence: 89%
“…Despite an enrichment in our cohort for inherited CRC and polyposis, the frequency (3 in 1188; 0.25%) is also comparable to the currently reported frequency. 13,14 The first patient (PT1) was diagnosed with a MSI caecum tumour and two adenomas at age 40. She developed, cumulatively, around 30 polyps and presented with a microsatellite stable endometrial cancer at age 50.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 3% of colorectal and 7% of endometrial cancers are reported with mutations in the proofreading domain of POLE (POLE-exo*) (The Cancer Genome Atlas Network 2012; Church et al 2013;Palles et al 2013;Kane and Shcherbakova 2014;Meng et al 2014;Valle et al 2014;Zou et al 2014). The mutation incidence in tumors with this defect often exceeds 100 mutations/Mb.…”
mentioning
confidence: 99%
“…Although some colorectal and endometrial tumors have been reported with POLD1 exonuclease mutations (POLD1-exo*) Valle et al 2014), their relationship to the mutational properties of those tumors is not clear. Preliminary data on survival of patients harboring mutations in POLE suggest they have significantly better outcomes (The Cancer Genome Atlas Network 2013; Meng et al 2014) and therefore may require less aggressive treatment.…”
mentioning
confidence: 99%
“…To this end, the term "polymerase proofreading-associated polyposis" (PPAP) has been suggested [52]. POLE and POLD1 mutations may be inherited or arise de novo [53]. Germline mutations in these two genes appear to be fairly rare, and relatively few syndromic patients have been identified to date.…”
Section: Pole/pold1-associated Syndromementioning
confidence: 99%